Focus on autism and other neurodevelopmental disorders - Ryabinin, Andrey E. (Genes, brain and behavior, 2022)
Experiments in this research area have to provide balanced tests across potential pathological factors, genetics, sex/gender, and ages of the studied subject. [...]effects of these factors have to be analyzed across more than one of phenotype in an attempt to distinguish which of the phenotypes reflect the potential main culprit in the development of the disorder. [...]knowledge about neurodevelopmental disorders is accumulated in a mosaic fashion: A study might analyze many factors, but not across multiple ages, or focus on only one measure of behavior, or, in contrast, analyze multiple behaviors, but not take into account genetics or sex of the subjects. Because of difficulty of interpreting such mosaic evidence, we especially value studies that managed to achieve balanced analysis of more than one factor and more than one behavioral measure in the same set of experiments. In their thorough study published in this issue, Martin and colleagues analyzed male mice of two genetic models of ASD in an extensive set of tests of nociceptive behaviors and emotional contagion of pain.4 They found that the mosaic evidence for the varied directions of altered nociception in ASD can be replicated within a single study and even within a single model of ASD. [...]BTBR mice, an idiopathic model of ASD, showed decreased sensitivity to mechanical, heat, and peripherally applied chemical stimuli but increased sensitivity to visceral sensation in acute tests. Detailed analyses of the vocalizations showed that the vocal repertoire of these mutant pups at postnatal day 8 was similar to that of PN10 and 12 of wildtype pups, paradoxically suggesting faster development to the more mature phenotype. Since appropriate separation-induced vocalizations are required for adequate feeding and growth of young pups, this deficiency would potentially affect their future development resulting in abnormalities across several cognitive and affective domains.